A holistic exploration of leadership development - B. Von Krosigk (South African Journal of Business Management, 2007)
Aligning body, mind and spirit, acquiring emotional intelligence, an unshakable belief in their own intuition and producing outcomes in the context of organisational abilities encompass the attributes of leaders that emerged from this holistic exploration of leadership development. Emotionally aware leaders demonstrated their authenticity and cared for peaceful process. In this exploration such leaders started at the bottom within their enterprise working their way up over time. Agreeableness and flexibility were the core competencies they developed amongst others. A complex mix of behaviour, thoughts and emotions were the specific leadership attributes that were found to differ for different organisations. These specific leadership attributes needed to fit with the character and dynamics of the organisation. Since leadership development was found to be a holistic character development over time leadership courses are recommended for all scholars and students, with a strong emphasis on self-development. A grounded theory approach to this holistic exploration of leadership development serves the community well, by promoting the emergence of grounded theories which are free from practical impossibilities.
Keywords: 650